Pengaruh model pembelajaran APIK berbasis kenthongan thek-thek terhadap penguatan karakter profil pelajar Pancasila siswa sekolah dasar - Pratik Hari Yuwono; Sony Irianto; Darodjat Darodjat; Tri Yuliansyah Bintaro (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aimed to examine the effect of the APIK learning model, which integrates appreciative, progressive, integrative, and diversity-oriented principles, based on the local musical tradition of kenthongan thek-thek, on strengthening the Pancasila Student Profile character of elementary school students. The study used a quasi-experimental method with a pretest-posttest control group design supported by qualitative data from observation and interviews. The participants were 60 fourth-grade students at SD Universitas Muhammadiyah Purwokerto, consisting of 30 students in the experimental group and 30 students in the control group. The experimental group received eight learning sessions using the APIK model based on kenthongan thek-thek, while the control group received conventional instruction. Data were collected using a validated Pancasila Student Profile character questionnaire, behavioral observation sheets, and semi-structured interviews. Quantitative data were analyzed using paired sample t-test and independent sample t-test, while qualitative data were analyzed thematically. The results showed that the experimental group increased from 68.4 to 85.2 with a significant difference, whereas the control group increased from 67.9 to 71.3 without a significant difference. The posttest comparison also showed a significant difference between groups. The qualitative findings confirmed that collective kenthongan thek-thek activities strengthened cooperation, tolerance, cultural appreciation, and creativity. The APIK model based on local culture is effective for strengthening character education in elementary schools.